SACBC Education for Democracy - Posters 1-10 (1994)
No.1 Multi-party negotiating proces. No.2 Proportional representation. No.3 The new parliament. No.4 Regional seats in the National Assembly. No.5 Makeup of the National Assembly. No.6 Makeup of the senate. No.7 The Executive. No.8 The Judiciary. No.9 The Constitution. No.10 The Bill of Rights.